Evaluating The Clinical Correlation Of Male Infertility With Bacterial Infection And Sperm Quality - Natikar, Jyothi A; Raj G M, Naveen; Pandey, Shikha; Asha G, Asha G; Gowda R, Yashica (Journal of Neonatal Surgery, 2025)
Introduction: Numerous factors trigger male infertility, including lifestyle, the environment, health, medical resources and pathogenic microorganism infections. Bacterial infections of the male reproductive system can cause various reproductive diseases. Male urogenital tract infection (UTI) is one of the leading causes of male infertility, as bacteria in semen samples can lower sperm quality. Aim and Objective: Evaluating the clinical correlation of male infertility with bacterial infection and sperm quality Material and Methods: This was a Cross-sectional study carried out in the Department of Pathology with collaboration to Department of Microbiology at a tertiary care centre for a period of 1 year i.e, November 2023 to November 2024. A total of 410 semen samples were collected, after informed written consent, from married males with the complaint infertility. Semen analysis was carried out according to the WHO guidelines. The specimens were processed as per the latest CLSI guidelines for isolation and identification of the organisms, followed by Antibiotic susceptibility testing. Results: In the present study a total of 410 semen samples were screened out of which 105 (25.6%) showed significant bacterial growth i.e. ≥ 103 bacteria/ml of semen ejaculate. The maximum number of cases was found in the age group of 26-30 years (48.9%) followed by 31-35 (25%) and least in the age group of 20-25 years of age and above 41 years of age with (6.5%). In our study 72 (17.5%) isolates were from the Gram positive cocci (GPC) and 33 (8%) isolates were from the Gram negative bacilli (GNB). In the present study it was observed that the commonest isolate was the Coagulase Negative Staphylococcus species (7.5%) followed by Enterococcus species (5.3%), Staphylococcus aureus with 3.6% and least for Streptococcus species with 0.9 %. In case of GNB the maximum isolates was from E.coli with 5.1% followed by Pseudomonas aeruginosa (2.9%). It was also noted that all the GPC isolates, were sensitive to Linezolid, Vancomycin and Teicoplanin, and most of them were sensitive to Nitrofurantoin. Among the GNB isolated, most were sensitive to Amikacin and Piperacillin- Tazobactum The maximum number of cases recorded was from the Oligozoospermia and least from Azospermia. Conclusion: Bacterial infection in the male reproductive system is one of the key factors affecting male fertility. The main factors leading to male sterility are inflammation of the reproductive system, injury of the male reproductive organ, and spermatogenesis disorder induced by pathogenic bacterial infection. Since bacteria can affect the quality of sperm because infections have been shown to have a negative impact on semen parameters. We strongly suggest increasing awareness among people and considering screening programs for patients seeking fertility both to avoid transmission and to improve fertility outcomes among them.